Samuel Balderrama: capstone - Balderrama, Samuel, artist (Colorado State University. Libraries, 2016)
The artist's statement: I started my academic career studying computer engineering but as my education continued my love of the arts and computers began to converge and the result was graphic design. As I work I find inspiration all around me. As a graphic designer my style needs to be versatile to best fit the needs of the client. I get my inspiration from the world around me. I use a variety of different materials and mediums in each project, my methods are consistent. Everything begins with an idea, sketches, and a rough concept design. From here the subject determines the finished, materials. Each project consists of multiple works, often in a range of media, grouped around a specific theme. When doing research and production new areas of interest arise and always lead to new bodies of work.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design